Odpowiedź :
Odpowiedź:
a) ( x² + ax - 1)*( x² + b x + 1) = [tex]x^4 + 2 x^3 + x^2 - 1[/tex]
[tex]x^4 +a x^3 - x^2 + b x^3 +a*b x^2 - bx + x^2 + a x - 1 = x^4 +2 x^3 + x^2 - 1[/tex]
[tex]x^4 + ( a + b) x^3 + a*b x^2 + (a - b ) x -1 = x^4 + 2 x^3 + x^2 - 1[/tex]
więc
a + b = 2 ⇒ b =2 - a
a*b = 1 ⇒a *( 2 - a) =1 ⇒ 2 a - a^2 = 1 ⇒ a^2 -2 a + 1 = 0 ⇒ (a - 1)² = 1
a = 1
1*b = 1 ⇒ b = 1
Odp. [tex]x^4 +2 x^3 + x^2 - 1 = ( x^2 + x - 1)*( x^2 + x + 1)[/tex]
=============================================
e) ([tex]x^2 + a x + 1)*( x^2 + b x - 5) = x^4 + x^3 - 6 x^2 - 11 x - 5[/tex]
[tex]x^4 + a x^3 + x^2 + b x^3 + a*b x^2 + b x -5 x^2 - 5a x - 5 = x^4 + x^3 - 6 x^2 - 11 x - 5[/tex]
[tex]x^4 + (a+b) x^3 + ( a*b -4) x^2 + ( b - 5 a) x - 5 = x^4 +x^3 -6x^2 -11 x - 5[/tex]
zatem
a + b = 1 ⇒b = 1 - a
a*b - 4 = - 6 ⇒ a*(1 - a) - 4 + 6 = 0 ⇒ a - a² + 2 = 0 ⇒
a² - a - 2 = 0 ⇒ ( a + 1)*(a - 2) = 0
a = - 1 lub a = 2
==================
wtedy
b = 1 - (-1) = 2 lub b = 1 - 2 = - 1
oraz b - 5 a = - 11
spr. 2 - 5*(-1) = 7 ≠ - 11 odpada
-1 - 5*2 = - 1 - 10 = - 11 ok
czyli
a = 2 i b = - 1
===================
Odp. [tex]x^4 + x^3 - 6 x^2 - 11 x - 5 = ( x^2 +2 x + 1)*(x^2 - x - 5)[/tex]
======================================================
Szczegółowe wyjaśnienie: